Case Report: A young man with frontal traumatic sinus pericranii - Zhang, Zihao; Hao, Qingpei; Luan, Ruirui; Qin, Guangbiao; Liu, Ruen (Frontiers in Surgery, 2024)
Sinus pericranii is a rare venous anomaly characterized by abnormal communication between intracranial and subperiosteal veins, and reports of trauma-induced sinus pericranii are even rarer. Herein, we report a case of delayed-onset sinus pericranii resulting from a traumatic injury to the left side of the midline of the forehead sustained in early childhood. The anomaly was successfully resected via a coronal incision within the hairline, followed by meticulous bone wax sealing. In this paper, we aim to provide details on the diagnosis and surgical techniques of trauma-induced sinus pericranii, contributing valuable insights for the management of such rare condition.